Gum Acacia Functionalized Colloidal Gold Nanoparticles of Letrozole as Biocompatible Drug Delivery Carrier for Treatment of Breast Cancer - Hibah M. Aldawsari; Sima Singh; Nabil A. Alhakamy; Rana B. Bakhaidar; Abdulrahman A. Halwani; Shaimaa M. Badr-Eldin (Pharmaceutics, 2021)
The most prevalent malignancy among postmenopausal women is breast cancer. It is one of the leading causes of cancer-related mortality among women. Letrozole (LTZ) is a clinically approved inhibitor for breast cancer in postmenopausal women. However, due to poor aqueous solubility, non-specific binding, unwanted toxicity, and poor blood circulation hampered its clinical applications. To maximize the pharmacological effects and minimize the side effects, inorganic nanoparticles are a good alternative. Due to excellent biocompatibility and minimum cytotoxicity, gold nanoparticles (AuNPs) offer distinct benefits over other metal nanoparticles. Emerging as attractive components, AuNPs and Gum acacia (GA) have been extensively studied as biologically safe nanomaterials for the treatment of cancers. This study reports the synthesis and characterization of GA stabilized gold nanoparticles (GA-AuNPs) of LTZ for breast cancer treatment. The observed particle size of optimized LTZ @ GA-AuNPs was 81.81 ± 4.24 nm in size, 0.286 ± 0.143 of polydispersity index (PDI) and −14.6 ± −0.73 mV zeta potential. The biologically synthesized LTZ @ GA-AuNPs also demonstrated dose-dependent cytotoxicity against the human breast cancer cell line MCF-7, with an inhibitory concentration (IC50) of 3.217 ± 0.247. We determined the hemolytic properties of the LTZ @ GA-AuNPs to evaluate the interaction between the nanoparticles and blood components. Results showed that there is no interaction between LTZ @ GA-AuNPs and blood. In conclusion, the findings indicate that LTZ @ GA-AuNPs has significant potential as a promising drug delivery carrier for treating breast cancer in postmenopausal women.